Beetham Beetham Beetham: Banal Luxury and ‘Quality Places’ - Jefferies, Tom (AESOP, 2010)
The UK has seen the longest period of boom in the construction industry since WW2, with continuous growth between 1993 and 2007, a context that dramatically and radically changed following the global financial crisis of 2008-09. The boom was characterised by a revived focus on the city centre as a space where regeneration of post-industrial cities could be catalysed in an environment that saw overt competition between cities to be the best. The boom also coincided with the raising in public consciousness of design as a qualitative and desirable commodity through exposure in popular media and encapsulation of ‘quality’ in political and policy objectives. This in turn has led to the introduction of new areas of built environment focussed policy and guidance aiming to ensure design ‘quality’ that embodies the values of ‘place’ in both urban space and built form. Place intersects the uniqueness of location with culture. This raises the question ‘If each city is different why are new places all so similar?’
Book of proceedings: Annual AESOP Congress, 2010 Space is Luxury, Aalto, July 7-10th
Keywords: placemaking; urban design; quality